Characteristics of breaking irregular wave forces on a monopile. (September 2019) - Aggarwal, Ankit; Bihs, Hans; Myrhaug, Dag; Chella, Mayilvahanan Alagan
Highlights: Numerical modelling of breaking irregular wave forces on a monopile. Validation of numerical model with experimental data. Correlation of free surface elevation skewness and spectral bandwidth with breaking wave forces. Role of the horizontal wave-induced water particle velocities at the free surface in breaking wave forces. Role of the wave pressure at the free surface in breaking wave forces. Abstract: The substructures of offshore wind turbines are subjected to extreme breaking irregular wave forces. The present study is focused on investigating breaking irregular wave forces on a monopile using a computational fluid dynamics (CFD) based numerical model. The breaking irregular wave forces on a monopile mounted on a slope are investigated with a numerical wave tank. The experimental and numerical irregular free surface elevations are compared in the frequency-domain for the different locations in the vicinity of the cylinder. A numerical analysis is performed for different wave steepness cases to understand the influence of wave steepness on the breaking irregular wave loads. The wave height transformation and energy level evolution during the wave shoaling and wave breaking processes is investigated. The higher-frequency components generated during the wave breaking process are observed to play a significant role in initiating the secondary force peaks. The free surface elevation skewness and spectral bandwidth during the wave transformation process are analysed and an investigation is performed to establish a correlation of these parameters with the breaking irregular wave forces. The role of the horizontal wave-induced water particle velocity at the free surface and free surface pressure in determining the breaking wave loads is highlighted. The higher-frequency components in the velocity and pressure spectrum are observed to be significant in influencing the secondary peaks in the breaking wave force spectrum.